2021
DOI: 10.3389/fimmu.2021.775708
|View full text |Cite|
|
Sign up to set email alerts
|

Dual RNA-Seq of Trunk Kidneys Extracted From Channel Catfish Infected With Yersinia ruckeri Reveals Novel Insights Into Host-Pathogen Interactions

Abstract: Host-pathogen intectarions are complex, involving large dynamic changes in gene expression through the process of infection. These interactions are essential for understanding anti-infective immunity as well as pathogenesis. In this study, the host-pathogen interaction was analyzed using a model of acute infection where channel catfish were infected with Yersinia ruckeri. The infected fish showed signs of body surface hyperemia as well as hyperemia and swelling in the trunk kidney. Double RNA sequencing was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Large-scale diseases can occur from time to time, resulting in significant economic losses in channel catfish culture ( 39 , 40 ). Del is not only an important pollutant in water but also an insecticide used in aquaculture, becoming an important factor affecting their healthy cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large-scale diseases can occur from time to time, resulting in significant economic losses in channel catfish culture ( 39 , 40 ). Del is not only an important pollutant in water but also an insecticide used in aquaculture, becoming an important factor affecting their healthy cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…We used quantitative reverse transcription (qRT)-PCR to verify the expression level of DEGs identified by RNA-Seq. The primers used are shown in Table 1 ( 39 , 44 50 ). Channel catfish EF-1 α was used as the internal parameter to homogenize the expression levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yersinia ruckeri (GenBank accession number is OL376599) [ 29 ] was reported in our previous study, and Streptococcus iniae was provided by Northwest A & F University. The bacteria were cultured on brain heart infusion (BHI) at 28 °C for 18 h to reach the logarithmic growth phase and were then rinsed with sterile phosphate buffer saline (PBS) and adjusted to a concentration of 1.5 × 10 7 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…These issues seriously limit the channel catfish industry's further development and have resulted in various disease outbreaks that have gradually become dangerous to channel catfish [7]. A previous study reported that infectious diseases cause great harm to channel catfish breeding, including bacterial [8,9], parasitic, viral, and fungal diseases, especially bacterial and viral diseases [10]. The main bacterial pathogens infecting channel catfish are Aeromonas hydrophila, Yersinia ruckeri, Edwardsiella ictaluri, and Streptococcus iniae, which have caused severe harm and economic loss to the aquaculture industry [9,11].…”
Section: Introductionmentioning
confidence: 99%